Experimental data on lithium salts: From neuroprotection to multi-organ complications - Kakhki, Samaneh; Ahmadi-Soleimani, S. Mohammad (Life sciences (1973), 2022)
Lithium-salts stand on the first line of therapy for the management of specific psychiatric conditions, mainly bipolar mood disorder. It is also known to protect the brain against neurodegenerative processes such as Alzheimer's disease. Despite the mentioned merits, recent studies have revealed that high dose or prolonged lithium intake deteriorate the function of multiple key organs including heart, ovaries, thyroid gland and kidneys. Mechanistically, both positive and negative effects of lithium are mediated through methylation of β-catenin nuclear-binding proteins which is potentiated by lithium-induced inhibition of GSK-3 or inositol monophosphatase. The current study briefly reviews the recent experimental data on lithium therapy considering both positive (i.e., neuroprotective) and negative aspects. In this regard, the question is that whether doses of lithium administered in experimental research are comparable with the therapeutic doses, as currently prescribed in clinical practice. It should be noted that the experimental data on animal studies, as widely reviewed here, could not be directly generalized to clinic. This is mainly because lithium doses applied in animal models are usually higher than therapeutic doses, however, there are evidence indicating that even animal to human translated doses of lithium, cause serious complications and this has been reported by meta-analyses on human studies. Therefore, we suggest the clinicians to use lithium-salts with precaution particularly in pregnancy and precisely adjust lithium concentration considering the patient's general health status to avoid lithium toxicity. Indeed, alternative approaches are recommended when the subject is pregnant, prolonged therapy is required or specific organ dysfunction is diagnosed. [Display omitted]